The Virtual Institute of Social Innovation at Production Engineering Department of Rio de Janeiro Federal University - Bartholo, Roberto; Campos, Arminda Eugenia [UNESP]; Sarayed-Din, Luiza; Baralt, J.; Callaos, N.; Chu, H. W.; Ferrer, J.; Tremante, A. (Int Inst Informatics & Systemics, 2010)
This article describes the process of creation of the Virtual Institute of Social Innovation at Rio de Janeiro Federal University. The 2004 Innovation Law requires that Brazilian universities establish Innovation Agencies, aimed at identifying the technological innovations created by their faculty and researchers and at providing juridical and technical support to the researchers in their relationships with the productive sector. Rio de Janeiro Federal University created a ground-breaking type of Innovation Agency, as, since its creation, it has a sector oriented to identifying, promoting and diffusing social innovations. This social innovation sector differs from the typical university department: the Social Innovation Virtual Institute is a web-based site, aimed at housing the work of a network of researchers, students, staff and non-academic people, interested in reflecting about the social innovations created in the University. The Institute also aims at communicating the results of the implemented innovations. It was designed as a communicative and collaborative platform, intended to enable the exchange, the construction and reformulation of different kinds of knowledge, through the dialogue between the academic world and civil society. The article presents the previous experiences who led to the creation of the Virtual Institute and the model designed for it.
Keywords: extension programs; innovation management; social innovation; collaborative knowledge-creation; enabling platforms